PEMBERIAN GULA AREN TERHADAP ORGANOLEPTIK NATA DE SAGO SEBAGAI RANCANGAN BOOKLET MATERI PELAJARAN BIOTEKNOLOGI TINGKAT SMA KELAS XII - Desi Putri Ayu; Nursal Nursal; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstrak: This research was conducted to determine the application of palm sugar to the organoleptic nata de sago and the design of biotechnology subject matter booklets for class XII high school level. This research was carried out in 2 stages, namely the experimental stage: the effect of palm sugar on the quality of nata de sago and the second stage of booklet design: analysis of the potential for developing teaching materials for biotechnology subject matter for class XII high school students. This study used an experimental method by conducting experiments at the Mathematics and Educational Sciences Education Laboratory (PMIPA), Pekanbaru. Sampling was carried out in a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The parameters in this study were thickness analysis, acidity (pH) analysis, and organoleptic tests. Based on the results of the Analysis of Variance (ANOVA) at the 5% level, palm sugar administration showed a highly significant different effect on the organoleptic of nata de sago. the administration of 100 grams of palm sugar gave the best increase in the quality of nata de sago and based on an analysis of the potential of the research results it could be used as a design material booklet for class XII high school biotechnology subjects.Kata Kunci : Organoleptik Nata de sago, Rancangan Booklet, Gula Aren